2012
DOI: 10.1128/jcm.05852-11
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Uncultivated Bacteria in the Adult Female Bladder

Abstract: c Clinical urine specimens are usually considered to be sterile when they do not yield uropathogens using standard clinical cultivation procedures. Our aim was to test if the adult female bladder might contain bacteria that are not identified by these routine procedures. An additional aim was to identify and recommend the appropriate urine collection method for the study of bacterial communities in the female bladder. Consenting participants who were free of known urinary tract infection provided urine samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
540
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 573 publications
(572 citation statements)
references
References 39 publications
24
540
1
7
Order By: Relevance
“…These culture-independent techniques hold great promise in advancing our ability to detect and study urinary bacteria. Such techniques have already shown that urine from asymptomatic women is often not "sterile" [3,20] and that voided urine of adult males contains diverse bacteria. In both cases, many of the bacteria identified cannot be or are not routinely cultivated by clinical microbiology laboratories [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These culture-independent techniques hold great promise in advancing our ability to detect and study urinary bacteria. Such techniques have already shown that urine from asymptomatic women is often not "sterile" [3,20] and that voided urine of adult males contains diverse bacteria. In both cases, many of the bacteria identified cannot be or are not routinely cultivated by clinical microbiology laboratories [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on DNA and culture have provided evidence of live bacteria in urine samples that are deemed "culture-negative" by standard clinical microbiological procedures [3,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given emerging evidence that documents the presence of urinary microbiota in many adult women (7)(8)(9)(10)(11)(12)(13)(14)(15), it is clear that the mere presence of an organism should not prompt antibiotic treatment. However, clinicians are likely to benefit from a more complete report of organisms present within a symptomatic patient's urine.…”
mentioning
confidence: 99%
“…Normal urine was assumed to be sterile, and patients diagnosed with UTIs had urine with bacterial counts of Ͼ10 5 CFU/ml. While this is still common practice today, Stamm et al reported documented UTIs in women with colony counts between 10 2 and 10 5 in 1982 (2), and more recently, the interpretation of urine culture results has been further complicated by reports that urine is not necessarily sterile (3,4). Moreover, diagnosis is even further complicated by the fact that urine samples are often contaminated with normal indigenous bacteria during the collection process.…”
mentioning
confidence: 99%